Legal Construction For The Obligors Of The Bank Of Indonesia Liquidity Assistance Funds (Blbi) In Returning State Assets That Guarantee Legal Certainty And Justice - Ardini, Aida (Journal of World Science, 2022)
The BLBI dispute has been running for more than 20 years since the BLBI issued by the Government during the monetary crisis that occurred in Indonesia from 1997 to 1998, when the Government of Indonesia decided to implement a managed floating exchange rate system and free floating Until now, theproblem of Bank Indonesia Liquidity Assistance (BLBI) has not yet been found. Even blbi dispute resolution is increasingly unclear in its direction. The deviation of BLBI disbursement amounted to Rp 138,442 trillion from the total BLBI funds issued by the Government to save the economic crisis that at that time occurred amounted to Rp 144,536 trillion. The urgency of legal reconstruction is very necessary in resolving disputes over BLBI funds that are increasingly directionless.